2016
DOI: 10.7554/elife.18065
|View full text |Cite
|
Sign up to set email alerts
|

Control of the structural landscape and neuronal proteotoxicity of mutant Huntingtin by domains flanking the polyQ tract

Abstract: Many neurodegenerative diseases are linked to amyloid aggregation. In Huntington’s disease (HD), neurotoxicity correlates with an increased aggregation propensity of a polyglutamine (polyQ) expansion in exon 1 of mutant huntingtin protein (mHtt). Here we establish how the domains flanking the polyQ tract shape the mHtt conformational landscape in vitro and in neurons. In vitro, the flanking domains have opposing effects on the conformation and stabilities of oligomers and amyloid fibrils. The N-terminal N17 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
119
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(130 citation statements)
references
References 102 publications
8
119
3
Order By: Relevance
“…However, recently published evidence indicates that the nature of the residues at the boundaries of polyQs can also strongly impact aggregation propensity. For instance, a proline homorepeat at the C-terminal of the Huntingtin protein-polyQ prevents aggregation while 17 residues with an overall positive charge at the N-terminus have the opposite effect, inducing stronger aggregation at neutral pH (Thakur et al, 2015;Shen et al, 2016). Similarly, the addition of two negatively charged residues at the amino end and two positively charged residues at the carboxyl end of the polyQ domain of the yeast Sup35 solubilizes the protein at acidic pH and aggregates at neutral pH while a polyalanine flanked by the same charged amino acid is soluble at all pH values (Perutz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, recently published evidence indicates that the nature of the residues at the boundaries of polyQs can also strongly impact aggregation propensity. For instance, a proline homorepeat at the C-terminal of the Huntingtin protein-polyQ prevents aggregation while 17 residues with an overall positive charge at the N-terminus have the opposite effect, inducing stronger aggregation at neutral pH (Thakur et al, 2015;Shen et al, 2016). Similarly, the addition of two negatively charged residues at the amino end and two positively charged residues at the carboxyl end of the polyQ domain of the yeast Sup35 solubilizes the protein at acidic pH and aggregates at neutral pH while a polyalanine flanked by the same charged amino acid is soluble at all pH values (Perutz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Using the associative memory, water-mediated interactions, structure and energy model (AWSEM), previous simulations by our group have successfully explained how the change of critical nucleus size arises from the differences in the propensity of monomeric polyQ repeats of different lengths to form β-hairpins: the longer repeats fold into hairpins intramolecularly before they aggregate (9). The aggregation of the diseasecausing peptide is, however, further complicated by the presence of flanking amino acid sequences in fragments encoded by HTT exon 1. Experiments indicate that the addition of NT17 at the N terminus of polyQ enormously accelerates the aggregation, probably by encouraging the formation of prefibrillar oligomers (10)(11)(12)(13)(14)(15)(16), whereas the addition of the proline-rich region at the C terminus decreases the rate of aggregation apparently without changing fundamentally the mechanism (10,16,17). Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation.…”
mentioning
confidence: 99%
“…An obvious candidate is the interaction with the valosin-containing protein which was mapped in the basic motif RKRR in the C-terminal tail (38). Our work will also potentially be important for the advance of ataxin-3 aggregation since a number of studies have shown that the regions immediately N-and C-terminal to the polyQ repeats play an important role in modulating protein self-assembly (39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 98%